Atmospheric acid leaching of oxidised and mixed copper cobalt ores mined in the Democratic Republic of the Congo - Pretorius, Petrus Johannes (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.